2017
DOI: 10.1099/mic.0.000497
|View full text |Cite
|
Sign up to set email alerts
|

Effective identification of Lactobacillus casei group species: genome-based selection of the gene mutL as the target of a novel multiplex PCR assay

Abstract: Lactobacillus casei,Lactobacillus paracasei and Lactobacillusrhamnosus form a closely related taxonomic group (the L. casei group) within the facultatively heterofermentative lactobacilli. Strains of these species have been used for a long time as probiotics in a wide range of products, and they represent the dominant species of nonstarter lactic acid bacteria in ripened cheeses, where they contribute to flavour development. The close genetic relationship among those species, as well as the similarity of bioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 55 publications
1
31
0
Order By: Relevance
“…Of the 29 strains belonging to L. rhamnosus, PCR products of the expected length could not be obtained in six cases (data not shown). Similar cases are also described by Bottari et al [33].…”
Section: Multiplex Pcrsupporting
confidence: 87%
See 2 more Smart Citations
“…Of the 29 strains belonging to L. rhamnosus, PCR products of the expected length could not be obtained in six cases (data not shown). Similar cases are also described by Bottari et al [33].…”
Section: Multiplex Pcrsupporting
confidence: 87%
“…On the other hand, especially for bacteria with high genetic similarity, the design and optimization of the reaction itself can be relatively difficult [31,32]. In this study, we used two sets of primers that were designed based on the tuf and mutL gene sequences (Table S1), to identify species of the L. casei group [16,33].…”
Section: Multiplex Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Multilocus sequence analysis based on 29 ribosomal proteins and 12 phylogenetic markers and phylogenetic tree construction. A maximum likelihood phylogeny was built from 29 ribosomal proteins and 12 housekeeping markers, which were chosen on the basis of their use in published multilocus sequence typing schemes and their presence in the genomes of the 222 strains (Table S2) (38).…”
Section: Methodsmentioning
confidence: 99%
“…Another MLST study of 224 L. casei isolates from fermented foods using 10 housekeeping genes found no correlation with geographic location or food source, implying a complex evolutionary history and contradicting previous studies ( Bao et al, 2016 ). Other single target genes used for species discrimination include housekeeping genes such as the chaperone protein gene, dnaJ ( Huang et al, 2015 ), dnaK ( Huang and Lee, 2011 ), yycH ( Huang et al, 2014 ), and mutL ( Bottari et al, 2017 ). Indeed, it was found that the dnaJ gene provided better resolution than the 16S rRNA subunit gene for comparisons within and between species, and this has been suggested as an alternative marker ( Huang et al, 2015 ).…”
Section: Current and Future Trendsmentioning
confidence: 99%